Language as a Tool of Empowerment: The Role of Communication Dynamics in Subaltern Voices - V, Devaki (CV. Creative Tugu Pena, 2024)
This study examines how language functions as a tool of empowerment within subaltern communities by focusing on the dynamics of communication. Drawing on concepts from subaltern studies and sociolinguistics, the research delves into how marginalized groups utilize linguistic tactics to defy dominant perspectives, assert their unique identities, and cultivate a sense of unity and connection within their communities. Subaltern studies have emerged as a response to the need for greater representation and recognition of these voices. The study of subaltern voices is significant in sociolinguistics because it highlights the power dynamics inherent in language use and communication. This study combines a wealth of existing literature with in-depth theoretical analysis to provide an extensive understanding of how communication dynamics can empower subaltern voices. The findings of this research not only contribute to academic discourse but also offer practical insights. They enhance our comprehension of the innate power in linguistic practices and emphasize the potential of language to challenge and change entrenched power systems. By analyzing how communication fosters empowerment, this study highlights the essential role of language as a means of resistance and resilience for subaltern communities. Ultimately, the research aims to foster a more inclusive and equitable society by amplifying marginalized voices and challenging dominant narratives through the transformative potential of language. Keywords: Sociolinguistic, Resistance and Empowerment, Discourses and Counter-Narratives, Language Adaptation Orchid ID: https://orcid.org/0000-0002-6091-3173